Bounding cross-shelf transport time and degradation in Siberian-Arctic land-ocean carbon transfer - Bröder, Lisa; Tesi, Tommaso; Andersson, August; Semiletov, Igor; Gustafsson, Örjan (Nature Communications, 2018)
The burial of terrestrial organic carbon (terrOC) in marine sediments contributes to the regulation of atmospheric CO 2 on geological timescales and may mitigate positive feedback to present-day climate warming. However, the fate of terrOC in marine settings is debated, with uncertainties regarding its degradation during transport. Here, we employ compound-specific radiocarbon analyses of terrestrial biomarkers to determine cross-shelf transport times. For the World's largest marginal sea, the East Siberian Arctic shelf, transport requires 3600 ± 300 years for the 600 km from the Lena River to the Laptev Sea shelf edge. TerrOC was reduced by ∼85% during transit resulting in a degradation rate constant of 2.4 ± 0.6 kyr -1 . Hence, terrOC degradation during cross-shelf transport constitutes a carbon source to the atmosphere over millennial time. For the contemporary carbon cycle on the other hand, slow terrOC degradation brings considerable attenuation of the decadal-centennial permafrost carbon-climate feedback caused by global warming.